2006
DOI: 10.1590/s0100-204x2006000800012
|View full text |Cite
|
Sign up to set email alerts
|

Fontes e doses de boro em porta-enxertos de seringueira

Abstract: Este trabalho teve por objetivo avaliar o efeito da aplicação de boro sobre o incremento do diâmetro do caule no ponto de enxertia, 5 cm acima do coleto, número e diâmetro de raízes laterais e estado nutricional de porta-enxertos para produção de toco enxertado de raiz nua. O delineamento experimental foi o de blocos ao acaso, em esquema fatorial 2x5: duas fontes (ulexita, 10% de B e ácido bórico, 17% de B) e cinco doses de B (0, 2, 4, 8 e 16 kg ha-1) com quatro repetições. Em condições edafoclimáticas locais,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
1
2
0
3
Order By: Relevance
“…The sources ensured the availability of nutrients at adequate levels during the development of the plant without causing phytotoxicity up to the maximum estimated rate (MER) of 4.6 mg.kg -1 . The lower RV under H 3 BO 3 at the highest B concentrations is related to the high-water solubility of this source, which allows for greater contact with the plant root system and a consequent increase in nutrient uptake (Moreira et al, 2006). The increase in RV up to the MER corroborates the arguments of Marschner (2012), who reported that the lack of B causes inhibition of root elongation due to problems observed during cell division and cell elongation, resulting in thick roots with low volumes and necrotic tips.…”
Section: Resultsmentioning
confidence: 99%
“…The sources ensured the availability of nutrients at adequate levels during the development of the plant without causing phytotoxicity up to the maximum estimated rate (MER) of 4.6 mg.kg -1 . The lower RV under H 3 BO 3 at the highest B concentrations is related to the high-water solubility of this source, which allows for greater contact with the plant root system and a consequent increase in nutrient uptake (Moreira et al, 2006). The increase in RV up to the MER corroborates the arguments of Marschner (2012), who reported that the lack of B causes inhibition of root elongation due to problems observed during cell division and cell elongation, resulting in thick roots with low volumes and necrotic tips.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the studies up to now presented here on the effect of increasing boron doses on crop development, Freitas et al (2006) assessed the effects of boron-induced deficiency on Passiflora edulis (passion fruit) plants and did not find a significant reduction in root dry mass. For rubber tree rootstock, Moreira et al (2006) studied different boron doses and found that high doses (8 mg dm −3 of boron) did not affect the number of roots.…”
Section: Resultsmentioning
confidence: 99%
“…Para avaliação dos teores foliares (Tabela 4), foram utilizados como referência os dados obtidos por Moraes et al (2011) Malavolta et al (1997) e Moreira et al (2006), eles podem ser considerados baixos. Tal resultado possivelmente deva-se a aspectos morfológicos, como o escleromorfismo foliar das folhas dos clones de H. rigidifolia e de H. guianensis com H. pauciflora, com folíolos rígidos e densa ramificação de nervuras secundárias e terciárias (Pires et al, 2002), o que pode ser caracterizado por menor teor de nutrientes e, além disso, com o calibre visivelmente mais grosso que os verificado nos folíolos mais tenros de H. brasiliensis, que também deve ter influenciado negativamente o teor foliar.…”
Section: Resultsunclassified